2001
DOI: 10.1161/01.atv.21.6.899
|View full text |Cite
|
Sign up to set email alerts
|

Small GTP-Binding Protein Ral Modulates Regulated Exocytosis of von Willebrand Factor by Endothelial Cells

Abstract: Abstract-Weibel-Palade bodies are endothelial cell-specific organelles, which contain von Willebrand factor (vWF), P-selectin, and several other proteins. Recently, we found that the small GTP-binding protein Ral is present in a subcellular fraction containing Weibel-Palade bodies. In the present study, we investigated whether Ral is involved in the regulated exocytosis of Weibel-Palade bodies. Activation of endothelial cells by thrombin resulted in transient cycling of Ral from its inactive GDP-bound to its a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 36 publications
2
44
0
Order By: Relevance
“…These findings show that both epinephrine-and thrombin-induced exocytoses of WPB coincide with the activation of the small GTPase Rap1. Remarkably, the kinetics of Rap1 activation in response to thrombin and epinephrine are very similar to that observed for the activation of the small GTPase RalA (12,34), suggesting that these two GTPases are activated in a coordinated fashion.…”
Section: Methodssupporting
confidence: 66%
See 1 more Smart Citation
“…These findings show that both epinephrine-and thrombin-induced exocytoses of WPB coincide with the activation of the small GTPase Rap1. Remarkably, the kinetics of Rap1 activation in response to thrombin and epinephrine are very similar to that observed for the activation of the small GTPase RalA (12,34), suggesting that these two GTPases are activated in a coordinated fashion.…”
Section: Methodssupporting
confidence: 66%
“…Previous studies have supported the concept that both signaling pathways converge at the level of the guanine exchange factor RalGDS (11). Subsequent activation of the small GTPase Ral promotes assembly of the exocyst complex and mediates phospholipase D 1 -facilitated fusion of WPBs with the plasma membrane (16,34). In this study, we show that Epac1, through the activation of the small GTPase Rap1, is crucial for epinephrine-but not for thrombininduced release of WPBs.…”
Section: Discussionmentioning
confidence: 71%
“…Both lysosomal and WPB compartments are calcium sensitive, and in endothelial cells this process can be blocked by NO, calcium chelators, 16 a 22-amino acid N-ethylmaleimide (NEM)-sensitive factor fused to a Tat-carrier peptide, 20 NEM itself, a dominant-negative Ral variant, 21 and a glycine-(Na-Et)lysine-proline-arginine (ITF 1697) peptide. 22,23 By pharmacologically manipulating exocytosis of these organelles and examining the integrity of glycocalyx in response to stressors we obtained the key test results for the proposed hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…20 NEM itself is also a potent inhibitor of exocytosis. de Leeuw et al 21 demonstrated that a small GTPbinding protein, Ral, is involved in exocytosis of WPBs and that expression of a dominant-negative Ral variant prevented it. Bertuglia et al 22 explored a lysine-proline motif encountered in several biologically active small peptides and synthesized a glycine-(Na-Et)lysine-proline-arginine (ITF 1697) peptide, with the biological half-life of 20 to 120 minutes, and demonstrated that it inhibits ischemia-reperfusioneinduced exocytosis of WPBs and protected pulmonary microcirculation by preventing increase in permeability, leukocyte and platelet adhesion, P-selectin, and vWF secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Matsushita et al (16) developed fusion polypeptides composed of a 22-amino acid N-ethyl-maleimidesensitive factor (a regulator of exocytosis) and a carrier peptide derived from the human immunodeficiency virus transactivating regulatory protein domain and demonstrated that inhibition of WPB exocytosis decreased leukocyte trafficking and peritonitis (7). de Leeuw et al (6) demonstrated that a small GTP-binding protein, Ral, is involved in exocytosis of WPB and that expression of a dominant-negative Ral variant prevented it. More recently, Bertuglia et al (4) explored a lysineproline motif encountered in several biologically active small peptides and synthesized a glycine-(N␣-Et)lysine-proline-arginine (ITF 1697) peptide, with the biological half-life of 20 -120 min, and demonstrated that it inhibits ischemia-reperfusion-induced exocytosis of WPB and protected pulmonary microcirculation by preventing increase in permeability, leukocyte and platelet adhesion, P-selectin, and von Willebrand factor secretion.…”
mentioning
confidence: 99%